Analytical Modeling of SON MOSFET and Realization Inverter Circuit for High Speed and Ultra Dense Low Power Circuits - Kousik Naskar; C.J. Clement Singh; Subir Kumar Sarkar (Журнал нано- та електронної фізики)
In the recent years, there has been considerable interest in the realization of high speed, small-size and low-power consuming devices and systems. As a consequence, the search for new principle of operation of the small-size, high speed and low-power device is becoming more and more important. In our earlier paper, it has been established that SON technology, not only improve the dc performance with reduce a short-channel effect and threshold voltage, it also improves the frequency response due to improvement in conductance and reduced parasitic effect. Further, it is already in our knowledge that SCEs are suppressed in dual material gate MOSFETs because of the perceivable step in the surface-potential profile, which screens the drain potential. The concept of dual material gate has been applied to SON MOSFETs structure and the features exhibited by resulting new SON structure has been examined for the first time by developing an analytical model and the result agree well with the MEDICI simulation values. In order to substantiate the merits of the proposed SON MOSFETs, a MOS Inverter is realized using the SON MOSFETs and its performance is investigated as an aid to the high-speed, ultra-dense and low-power circuit related work.